Implementasi Metode COPRAS Dalam Pemilihan Sepeda Motor - Aris Munandar, Muhammad; Setyawan Wibisono (Elkom: Jurnal Elektronika dan Komputer, 2022)
Interest in buying a motorcycle is certainly caused by various criteria, from the criteria of brand, model, type, price, engine capacity, transmission, braking, year of manufacture and fuel consumption. Of the many criteria, of course, makes buyers get a variety of choices according to their wishes. However, in practice, there are difficulties in determining the criteria in the selection of motorcycles because many consumers do not understand the criteria for motorcycles. The weight of the assessment criteria for the COPRAS method for choosing motorcycles are namely price criteria weighing 40%, fuel consumption weighing 30%, engine capacity weighing 20% ​​and year of manufacture weighing 20%. The recommendation results from the selection of criteria for the Honda brand, type of scooter, automatic transmission and single disc braking, the recommendation results obtained are Beat Street with a value of 1,000, Genio with a value of 0.995, Scoopy with a value of 0.929, Vario 150 with a value of 0.866, PCX with a value of 0.812 and ADV with a value of value 0.796.